Equal split in the informal market for group train travel - Waichman, Israel; Requate, Tilman; Korzhenevych, Artem (Economics letters, 2013)
In this paper, we make use of a unique dataset collected at the central train station of the city of Kiel, Germany. Group tickets are used by individual proposers looking for co-travelers to share the ride with shortly before the train departure. The shared ride is offered for a fixed price. We observe that the prevailing price offer corresponds to an equal split of the ticket cost between the maximum possible number of co-travelers. This result is remarkable, because the positions of the bargaining parties are clearly asymmetric and formation of the full group is not guaranteed.